Internacionalizações rápidas na indústria da iluminação decorativa : estudos de caso em Portugal e no Reino Unido - Silva, Pedro Miguel Carvalho da (2021)
The rapid internationalization of companies is a phenomenon that, over the years, has gained more and more traction within the scientific community (Zahra, 2005; and Coviello, 2015). Even with the growth of curiosity for this peculiar aspect of internationalization, the creative industries rarely show themselves as the focus of these studies, with a tendency for traditional and technological industries to exist. The study of this phenomenon was popularized by Oviatt and McDougall in 1994, who, by identifying research gaps within the study of the internationalization process of companies, decided to orient their research in order to try to fill these gaps. This mfa serves the same purpose. Since there is a flaw in the study of the theme of rapid internationalization in the creative industries, more specifically in the decorative lighting industry, it is necessary to make their stories, processes and similarities known. Thus, it is important to ask ourselves about the phenomenon of rapid internationalization in the decorative lighting industry. To answer this question, two companies were chosen, one English and one Portuguese, in order to become aware of their different experiences and business realities that brought about the same end: rapid internationalization. The result obtained from the analysis of the case studies made it possible to find similarities between the companies and the bibliographic review carried out that served as support for this mfa. We can also conclude that, even companies with different economic and temporal realities and different internationalization processes, but with a business mindset and equal goals, end up becoming highly internationalized in a short period of time.